Literature, sense and imagery: some aspects - Suttana, Renato Nésio (Revista de Letras, 2015)
Since ancient Greece, the relationship between literature and the imagery has been an object of wondering of many thinkers. Beginning with Aristotle, and going on with Kant, Sartre and Blanchot, the effort to understand how the literary language becomes an “image” and, at the same time, maintains its capacity to express meaning outside of a dependency (where image refers to the universe of visual representations), constitutes a challenge. In this relation, we understand that the term image assumes initially a metaphorical character, which makes it necessary to inquire how the visual concept enters the field of language and becomes in it an element of meaning. In this paper, we discuss some aspects that issue. Based on the concept – suggested by Valéry – that there is in literature an element of construction and forethought –, which is immediately converted, in the act of reading, in a field of literary meaning, often surpassing the author’s intentions –, we walk toward the idea that there is, in the transforming process (of image in literature), a formation of sense that supports and justifies the reader’s interest in the dispersion of literary language, also opening the space of questioning and criticism. Conceptualizing the notion of sense is fundamental here. In this study, by defending the idea that the imaginary, in the notion of sense, is a mode of loss, of self-forgetting, we freely address some elements of the relationship between literature and imagery, as well as its importance to criticism and literary interpretation.